Relações entre o consumidor e o sistema bancário: considerações legais e éticas sobre publicidade e oferta de crédito responsável - Paes, Marcela Papa (2023)
Advertising is a mass social communication tool fully inserted into people’s lives. Its aim is to persuade and convince the consumer to complete the purchase of a product or service made available in the market. By way of this research, we shall analyze the sophisticated advertising tools used in sales strategies. These aim to interfere in the architecture of choices to result in unexpected contracts, notably related to banking advertising. Using the historical deductive method and bibliographical research, it is observed that banking advertising is a relevant form of communication for credit agreements, and many times the first between the supplier and the consumer. Following the understanding that the offeror is bound by his own offer, pursuant to the provisions of the Federal Statute Law n. 14,181/2021, regarding super-indebtedness, it imposes upon banking service providers to act in a way that better details the information provided, to lower the effect of euphoria and irrationality resulting from persuasive advertising. In order to balance the relationship between the bank credit provider and its consumer, to avoid the consumer’s ruin and its super-indebtness, duties and requirements of responsible credit availability are imposed. This research led to the understanding that in parallel with responsible credit practices and with a view to promoting conscious consumption, and rational acceptance as result, it becomes immediate the necessity to raise the standard of banking services in terms of upgrading the persuasion mechanisms utilized in publishing strategies and in aggressive marketing campaigns. Finally, the aim is to promote effective consumer protection, ensuring mechanisms of rationality for them, in order to secure a real conciseness of intent, essential element of contract formation, safekeeping a reflexion period, a previous offer for maturing and the right of withdrawal in banking credit agreements.